Trapline foraging by nectar-collecting hornets - Mathilde Lacombrade; Kristine Abenis; Charlotte Doussot; Loïc Goulefert; Kenji Nanba; Jean-Marc Bonzom; Mathieu Lihoreau (Animal Cognition)
Abstract Many bees, butterflies, birds, bats and primates are known to forage on familiar plant resources by visiting them in a stable and repeatable order called “traplines”. Here we report the existence of trapline foraging in wasps, the Japanese yellow hornets. We monitored the movement patterns of wild individually marked hornets collecting sucrose solution on four artificial flowers placed in their home range. After thirty consecutive foraging bouts, all the hornets had developed a repeatable flower visitation sequence. Using two different arrays of flowers, we also show that hornets consistently increased their foraging efficiency with experience. However, they did not always use the shortest path to visit all the flowers, often favoring movements between nearest-neighbour options rather than minimizing overall travel distance. Our study thus adds nectar-foraging wasps to the list of animals that exhibit trapline foraging, thereby significantly broadening the scope for comparative research in multi-destination route learning and memory.